Er maskinoversetting fra nordsamisk nyttig for sørsamisk? - Antonsen, Lene (Septentrio Academic Publishing, 2023)
The article assesses the strengths and weaknesses of a rule-based translation program from North Saami to South Saami. As a tool for translators, the system can contribute to more text being produced in South Saami, both by using North Saami as an intermediary in the translation of texts from Norwegian and Swedish, and by translating texts that are originally written in North Saami. The system may also help teachers in academia to understand texts written by South Saami students. The system is still not good enough, in particular the number of word pairs in the lexicon must be increased considerably to get a better result. The translation is also not robust with respect to linguistic errors in the North Saami text. The linguistic difference between North Saami and South Saami syntax is big, and one could consider whether it would be appropriate to use a rule-based approach, which allows using information about the sentences' dependency trees, in order to more easily transform the sentences from North Saami syntax to acceptable South Saami. Artikkelen vurderer sterke og svake sider ved et regelbasert oversettingsprogram fra nordsamisk til sørsamisk. Som verktøy for oversettere kan systemet bidra til at det blir produsert mer tekst på sørsamisk, både ved å bruke nordsamisk som et mellomledd i oversetting av tekster fra norsk og svensk, og ved å oversette tekster som originalt er skrevet på nordsamisk. Systemet er også til hjelp for lærere i akademia å forstå tekster skrevet av sørsamiske studenter. Systemet er enda ikke godt nok, spesielt må antall ordpar i leksikonet økes betraktelig for å få et bedre resultat. Oversettinga er også lite robust for språklige feil i den nordsamiske teksten. Det er så stor forskjell mellom nordsamisk og sørsamisk syntaks, at man bør vurdere om det vil være hensiktsmessig å bruke en regelbasert tilnærmingsmåte hvor man også kan bruke informasjon om setningenes dependenstre, for lettere å transformere setningene fra nordsamisk syntaks til akseptabel sørsamisk.